"Being in the zone": A systematic review on the relationship of psychological correlates and the occurrence of flow experiences in sports` performance - Stamatelopoulou, F.; Pezirkianidis, C.; Karakasidou, E.; Lakioti, A.; Stalikas, A. (Psychology, 2018)
Previous research has highlighted the role of internal states in the experience of flow in the sports performance context. This systematic review investigates the relationship between psychological correlates, personality dispositions, traits and internal states (motivation, goals, focus, and arousal) with the experience and occurrence of flow in professional athletes. There have been identified 17 studies published between 2012 and 2017 updating and extending Swann, Keegan, Piggott and Crust`s (2012) systematic review. The results indicate that specific psychological correlates, personality traits and dispositions, and internal states are strongly correlated with the appearance of flow. The present study adds to the current research on the sports` flow experience highlighting the importance of constructs, such as confidence, anxiety, commitment, motives, goals, attention, optimal focus and arousal, and the "letting it go" state.